Radiance to Reflectance Conversion Effects on Landsat TM Images - Saleh, Salah; AL-Kabi, Enaam; Karm, Nehad (Iraqi Journal of Science, 2025)
In this research digital nümbers (DNS) for Landsat-5 IM Images was converted to reflectance values, at first DNs converted to radiance by corrected for Gain and Offset values of the particatur spectral IM band Then converted these radiance values to spectral reflectance by correcting the atmospheric effects. to study the e foots of the conversion, digital image processing techniques were applied for both mages (DNs and Reflectance), suult as enhancement by histogram cqualization, and geometrical correction Imirge classification (supervised and unsupervised) also applied us comparative criteria. The analysis of the results shows that the reflectance image gave bette: classification nocuracy for supervised and unsupervised chusentication than image DNs while conversion Dis to reflectance image does not effort ins geometrical properties.